Respuesta :
Answer: Option D
[tex]f(x)=(x+3)^2 -k[/tex]
Step-by-step explanation:
For a quadratic function of the form
[tex]ax ^ 2 + bx + c[/tex]
The x coordinate of the vertice is:
[tex]x =-\frac{b}{2a}[/tex]
In this case the function is:
[tex]f(x)=x^2+6x-2\\\\[/tex]
So
[tex]a=1\\b=6\\c=-2[/tex]
The x coordinate of the vertice is:
[tex]x=-\frac{6}{2*1}\\\\x=-3[/tex]
The y coordinate of the vertice is:
[tex]f(-3) = (-3)^2 +6(-3) -2\\\\f(-3)=-11[/tex]
The vertice is: (-3, -11)
The form e vertice for a quadratic equation is:
[tex]f(x)=(x-h)^2 +k[/tex]
Where
the x coordinate of the vertice is h and the y coordinate of the vertice is k.
Then h=-3 and k =-11
Finally the equation [tex]f(x)=x^2+6x-2\\\\[/tex] in vertex form is:
[tex]f(x)=(x+3)^2 -k[/tex]
Answer:
The correct answer option is D. f(x) = (x + 3)² - 11.
Step-by-step explanation:
We know that the standard form of a quadratic function is given by:
y = ax² + bx + c
The vertex form of a parabola is given by
y = a(x - h)² + k
where (h, k) is the vertex of the parabola.
h = -b / 2a and k = f(h)
In the given equation f(x) = x² + 6x - 2
a = 1, b = 6 and c = -2
Finding h:
h = -6 / (2 × 1)
h = -6/2
h = -3
Finding k:
k = 1(-3)² + 6(-3) + 3
k = 9 - 18 - 2
k = -11
Therefore, the given quadratic function in vertex form: f(x) = (x + 3)² - 11